India's Chandrayaan Missions: Exploring the Moon for Science and Resources ... - George, Dr.A.Shaji (Zenodo, 2023)
India's space program has made rapid advances in recent decades, with a focus on exploring the Moon through the Chandrayaan series of lunar orbiter missions. Chandrayaan-1, launched in 2008, was India's first mission to the Moon. Its objectives included high-resolution mineralogical and chemical mapping, searching for surface or sub-surface water ice, and studying the lunar interior. Chandrayaan-1 operated for 312 days, achieving most of its goals while confirming the widespread presence of water molecules on the Moon before the mission ended prematurely. The Chandrayaan-2 mission aimed to land a rover on the lunar surface to conduct in-situ studies, but the landing attempt in 2019 was not successful. The proposed Chandrayaan-3 aims to try again to land near the lunar south pole, where permanently shadowed craters are believed to contain water ice - a valuable potential resource for sustained lunar habitation. The scientific payloads on Chandrayaan-3 are designed to study lunar topography, mineralogy, ...